STUDENTS’ PERCEPTIONS OF THE USE OF ORAL PRESENTATION AS A METHOD OF LEARNING - Cempaka, Adisti Gilang; Anjanie, Anjanie (Jurnal Ekonomi dan Bisnis Terapan, 2020)
The concept of active learning encourages students’ autonomy and their ability to learn and helps students to become